Social Presence in Computer-Mediated Communication between Gen X and Gen Z through WhatsApp - Akhirin, Oktariani; Palupi, P (Universitas Muhammadiyah Surakarta, 2022)
Purpose :The purpose of this study is to investigate how social presence is exhibited between members of Generation X and Generation Z through text-based communication on the WhatsApp platform. Research data was collected through in-depth interviews conducted with 4 pairs of parents and children who represent members of Generation X and Generation Z, respectively. Additionally, data was gathered through documentation. Methodology : This research employed a qualitative descriptive methodology, utilizing both inductive and descriptive data analysis approaches. The study utilized purposive sampling to ensure comprehensive and in-depth data collection. Applications/Originality/Value: Findings reveal that both generations strive to establish intimacy, as reflected in their communication intensity, use of emojis or stickers, and sharing of pictures related to activities through WhatsApp. Furthermore, members of Generation X and Generation Z demonstrate immediacy in their response to family messages, make calls to convey their emotions or feelings, and respond promptly to critical situations.